EFFECTIVE METHODS OF FORMING INDEPENDENT WORK SKILLS OF STUDENTS OF ACADEMIC LYCEUMS - Хошимова Севара Шералиевна (Scholars Digest Publishing, 2023)
This article discusses the importance of improving the methodology for the formation of skills for independent activity of students of academic lyceums, which is an urgent and important task in the modern educational system. Academic lyceums have a high level of educational standards, and, accordingly, students of this type of school must have certain independent work skills that will help them study and develop successfully.
Keywords: Academic lyceums, improvement of methodology, modern educational system, independent work skills, development of information skills.